Mononuclear cells from patients with the hyperimmunoglobulin E-recurrent infection syndrome produce an inhibitor of leukocyte chemotaxis. - H Donabedian; J I Gallin (The Journal of Clinical Investigation, 1982)
The chemotactic responsiveness of the neutrophils of 10 patients with the hyperimmunoglobulin E-recurrent infection syndrome (HIE) were compared with neutrophils from normal volunteers over a 10-mo period. HIE neutrophils as a group displayed significantly less chemotactic motility than control neutrophils. The data from individual patients were variable, being normal or abnormal on different days. Mononuclear cells from HIE patients, when cultured for 24 h in the absence of serum or a mitogen, produced a factor that inhibited normal neutrophil and monocyte chemotaxis. Mononuclear cells from normal volunteers with and without atopy or from patients with parasites or bacterial infections did not produce such an inhibitory factor. The production of this chemotactic inhibitory factor in vitro was variable over time, but it correlated with the presence of an in vitro neutrophil chemotactic defect. The chemotactic inhibitory factor was partially purified and was found to contain protein, to be stable at 56 degrees C, and to have a molecular weight of approximately 61,000. Irreversible inhibitors of serine esterases do not inactivate the factor. The factor is produced by esterase-negative mononuclear cells and is not toxic to neutrophils. This chemotactic inhibitory factor may be the basis of the variable chemotactic defect in HIE neutrophils.